Study on a Frequency Fluctuation Attenuation Method for the Parallel Multi-VSG System - Sun, Zhenao; Zhu, Fanglin; Cao, Xingchen (Frontiers in Energy Research, 2021)
Virtual synchronous generator (VSG) is one of the inverter control methods which can provide extra virtual moment of inertia and achieve frequency support by mimicking the output characteristics of a rotating synchronous generator (RSG), which makes VSG particularly suitable for multi-access point applications, or called the multi-VSG system. However, frequency fluctuations may often occur in the case of power variation. In terms of this issue, this study presents the small-signal state-space model of VSG and analyzes the cause of frequency fluctuation, first. And then, a novel VSG control method is proposed for frequency fluctuation attenuation. The proposed method is especially fit for the parallel multi-VSG system because it does not take grid angular frequency into computation so that it can get rid of the ill effect introduced through PLL. The damping power item is reconstrued with a new means to judge whether the system is in a steady state or not. At the same time, the parametric design method of the proposed method is also figured out. Finally, the simulation experiments are performed, and the results verify that the proposed method performs better than the conventional one in terms of dynamic response and power-sharing among the multi-VSG system.